Prognostic humility and ethical dilemmas after severe brain injury: Summary, recommendations, and qualitative analysis of Curing Coma Campaign virtual event proceedings - Kreitzer, Natalie; Murtaugh, Brooke; Creutzfeldt, Claire; Fins, Joseph J.; Manley, Geoff; Sarwal, Aarti; Dangayach, Neha (Frontiers in Human Neuroscience, 2023)
Background Patients with severe acute brain injuries (SABI) are at risk of living with long-term disability, frequent medical complications and high rates of mortality. Determining an individual patient’s prognosis and conveying this to family members/caregivers can be challenging. We conducted a webinar with experts in neurosurgery, neurocritical care, neuro-palliative care, neuro-ethics, and rehabilitation as part of the Curing Coma Campaign, which is supported by the Neurocritical Care Society. The webinar discussed topics focused on prognostic uncertainty, communicating prognosis to family members/caregivers, gaps within healthcare systems, and research infrastructure as it relates to patients experiencing SABI. The purpose of this manuscript is to describe the themes that emerged from this virtual discussion. Methods A qualitative analysis of a webinar “Prognostic Humility and Ethical Dilemmas in Acute Brain Injury” was organized as part of the Neurocritical Care Society’s Curing Coma Campaign. A multidisciplinary group of experts was invited as speakers and moderators of the webinar. The content of the webinar was transcribed verbatim. Two qualitative researchers (NK and BM) read and re-read the transcription, and familiarized themselves with the text. The two coders developed and agreed on a code book, independently coded the transcript, and discussed any discrepancies. The transcript was analyzed using inductive thematic analysis of codes and themes that emerged within the expert discussion. Results We coded 168 qualitative excerpts within the transcript. Two main themes were discussed: (1) the concept of prognostic uncertainty in the acute setting, and (2) lack of access to and evidence for quality rehabilitation and specialized continuum of care efforts specific to coma research. Within these two main themes, we found 5 sub-themes, which were broken down into 23 unique codes. The most frequently described code was the need for clinicians to acknowledge our own uncertainties when we discuss prognosis with families, which was mentioned 13 times during the webinar. Several strategies were described for speaking with surrogates of patients who have had a severe brain injury resulting in SABI. We also identified important gaps in the United States health system and in research to improve the care of patients with severe brain injuries. Conclusion As a result of this webinar and expert discussion, authors identified and analyzed themes related to prognostic uncertainty with SABI. Recommendations were outlined for clinicians who engage with surrogates of patients with SABI to foster informed decisions for their loved one. Finally, recommendations for changes in healthcare systems and research support are provided in order to continue to propel SABI science forward to improve future prognostic certainty.